2004
DOI: 10.1521/aeap.16.2.126.29391
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing in a Resource-Poor Urban Emergency Department

Abstract: In an effort to help fight the HIV epidemic, we offered standard HIV testing to high-risk and symptomatic patients attending an urban emergency department (ED) located in a high-prevalence area. We assessed rates of consent, HIV infection, and linkage into care by demographic and risk characteristics. Consent rates were consistently greater than 50% across the various demographics and risk groups. The HIV prevalence rate was 3% and ranged from 0% to 50% across groups. Of those eligible to enter care 69% attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…1 EDs are desirable locations for HIV screening, as shown by research demonstrating that EDs in some communities provide medical care for large numbers of undiagnosed HIV-infected people [2][3][4][5][6][7][8] and those at risk of HIV infection. [2][3][4]6,7,9,10 Additionally, many EDs in the U.S. provide care for people without regular sources of medical care who might not get tested for HIV elsewhere. 11,12 Although HIV screening in EDs might be a good idea, patient acceptance of ED HIV screening has not been fully elucidated.…”
Section: Public Health Reports / 2008 Supplement 3 / Volume 123mentioning
confidence: 99%
See 1 more Smart Citation
“…1 EDs are desirable locations for HIV screening, as shown by research demonstrating that EDs in some communities provide medical care for large numbers of undiagnosed HIV-infected people [2][3][4][5][6][7][8] and those at risk of HIV infection. [2][3][4]6,7,9,10 Additionally, many EDs in the U.S. provide care for people without regular sources of medical care who might not get tested for HIV elsewhere. 11,12 Although HIV screening in EDs might be a good idea, patient acceptance of ED HIV screening has not been fully elucidated.…”
Section: Public Health Reports / 2008 Supplement 3 / Volume 123mentioning
confidence: 99%
“…U.S. ED-based voluntary HIV testing studies have reported a wide range of estimates of the proportion of patients (29.0% to 98.3%) accepting HIV testing in EDs. 2,3,[5][6][7]9,[13][14][15][16][17] (A summary of these published reports of U.S. ED HIV testing programs from 1993 through 2007 can be found at http://www.brown .edu/Departments/BRUNAP/US_ED_HIV_screening _programs.pdf.) All of these testing programs employed some variation of an opt-in approach in which patients were asked if they would like to be tested, as opposed to an opt-out approach in which patients were informed they would be tested unless they declined.…”
Section: Public Health Reports / 2008 Supplement 3 / Volume 123mentioning
confidence: 99%
“…Past efforts have centered primarily on the feasibility and yield of conducting HIV testing in this specific clinical environment, [8][9][10][11][12][13][14][15][16][17][18][19] and several ED-based rapid testing strategies have attempted to increase the yield of patients diagnosed with HIV infection. 8,9,[12][13][14][15][16][17][18]20 In recent years, rapid HIV testing methods have been proposed and evaluated in a growing but still limited fashion. A recently published paradigm categorized ED-based rapid HIV testing into diagnostic testing (i.e., testing based on clinical signs or symptoms), targeted testing or screening (i.e., testing a population based on specific risk characteristics), or nontargeted screening (i.e., testing a population regardless of risk).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] HIV infection is, however, increasing among populations that were not considered high-risk populations, such as young people, women, racial and ethnic minorities, persons residing outside metropolitan areas, and heterosexual men and women who are frequently unaware of their HIV risk. 11 Thus, in 2006, the Centers for Disease Control and Prevention (CDC) changed their previous recommendation on risk-based HIV testing in health care settings.…”
mentioning
confidence: 99%